Low power Analog Digital Converter for a silicon photomultiplier readout ASIC - Briggl, Konrad; Chen, Huangshan; Shen, Wei; Schultz-Coulon, Hans-Christian (Journal of Instrumentation, 2015)
We present an ADC designed in the UMC 0.18um CMOS technology. It will be used in the SiPM analog front-end “KLauS" developed for the analog hadronic calorimeter at ILD. Key parameter in this application is an extremely low power consumption of the front-end electronics. For quantization of the energy depositions, a 10-bit ADC resolution is required. For calibration purposes, a 12-bit quantization is used. A successive approximation register split capacitor array structure is chosen to minimize the DC power consumption. A peak sensing block is used to minimize the required sampling rate. We present design details and simulation results of the ADC, as well as the peak sensing track & hold circuit.
Gesehen am 28.05.2020